Environmental Education for Early Childhood Through Planting Activities in Khansa Kindergarten (TK Khansa) Medan - Rahmawaty, Rahmawaty (Talenta Publisher Universitas Sumatera Utara, 2020)
The school garden can be used for planting various types of plants. So that the use of land is more optimal, then one of the efforts that can be done is to invite students to plant various types of plants, such as vegetables, ornamental plants and fruits as well as medicinal plants. These plants can be placed in the school garden, both in the front and in the back. This activity aimed to provide environmental education for early childhood through planting various types of plants and introducing various types of plants in early childhood and to increase the type of vegetation/plants in the front and back yards of TK Khansa to make it look greener and more beautiful. There were some steps of activities, namely: preparation of planting media, planting, and harvesting of fast-growing type of vegetables. Based on the results of the activities, that the children were very enthusiastic and very happy through planting various types of plants in their school grounds. In addition, with this activity, the situation and the conditions in the Khansa Kindergarten School environment becomes more beautiful with the planting of various plants in the front and back yards of the school and become comfortable with the presence of various types of flowers and other plants.